Letter (copy) : International Brigade - Tewson, Vincent
034-0151-001 The Opera House, Winter Gardens, BLACKPOOL. Miss Charlotte Haldane, The International Brigade, 1, Litchfield Street, W.C.2. 7th September, 1938. Dear Miss Haldane, INTERNATIONAL BRIGADE. Your letter of the 2nd instant has now been considered by the General Purposes Committee of Congress and I have to convey to you their decision which is that they cannot accede to the request contained in your letter. Yours faithfully. Assistant Secretary. 292/946/34/151